THE ROLE OF ISLAMIC CORPORATE GOVERNANCE IN REDUCING SHARIA BANK FINANCING RISK IN INDONESIA - Khansa Sabihah; Mutamimah Mutamimah; Pungky Lela Saputri; Dedi Rusdi; Mariam Setapa; Amnisuhailah Abarahan (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
This study examines Islamic Corporate Governance (ICG), proxies by Sharia Supervisory Board, in mitigating the negative impact of Murabahah, Mudharabah, and Musyarakah financing on Non-Performing Financing (NPF) in Indonesian Islamic banks (2012–2023). This study employs purposive sampling to analyze 132 Islamic bank data from the Financial Services Authority (OJK) (2012–2023). Using Moderated Regression Analysis (MRA) the model testing panel static regression model by adding ICG as moderating variable. Murabahah, musharakah, and mudharabah significantly increased NPF, indicating the high financing risk of these contracts. ICG has a significant direct effect on lowering NPF, but does not moderate the relationship between financing and NPF significantly. This shows that increasing the number of ICG without adequate quality and coordination is not effective in strengthening the supervisory function, because it can cause overlapping tasks, coordination problems, and free riding behavior which actually weakens financing risk control. In summary, bank’s need to maintain their financing, especially for Murabaha and Musyarakah products. Further, considering to choosing expert ICG might help banks to break the NPF. The implication of this study is that while different sharia financing schemes significantly affect credit risk in Islamic banking, the Sharia Supervisory Board plays a crucial yet non-moderating role, highlighting the need to enhance its authority and operational involvement to strengthen risk mitigation efforts.